Pengaruh Green Product Dan Green Advertising Terhadap Keputusan Pembelian Fore Coffee Wilayah Jakarta Barat: The Influence of Green Products and Green Advertising on Fore Coffee Purchasing Decisions in West Jakarta - Hasanah, Uswatun; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The ever-increasing accumulation of waste each year has created a concerning condition for the planet. Consequently, many companies have adopted sustainability principles in their business operations. Fore Coffee is one such business that implements green marketing as a core principle. This research aims to determine whether green products and green advertising have a positive and significant influence on purchasing decisions, both partially and simultaneously. This study utilized questionnaires and documentation to collect the necessary data. The results of this research indicate that green products and green advertising have a positive and significant effect on purchasing decisions, both partially and simultaneously. This is evidenced by the green product variable yielding a t-value of 8.014, which is greater than the t-table value of 1.984, with a significance level of 0.000 < 0.05. Similarly, green advertising also shows a positive and significant influence on purchasing decisions. This is demonstrated by its t-value of 6.835, which is greater than the t-table value of 1.984, and a significance level of 0.000 (< 0.05). The simultaneous test also reveals that green products and green advertising jointly have a positive and significant influence on purchasing decisions, with a calculated F-value of 39.891, which is greater than the F-table value of 3.09